Current Perspectives in Human Papillomavirus 2019
DOI: 10.5772/intechopen.80654
|View full text |Cite
|
Sign up to set email alerts
|

Role of Extracellular Vesicles in Human Papillomavirus-Induced Tumorigenesis

Abstract: Emerging evidence demonstrates a role of extracellular vesicles (EVs) in a variety of fundamental physiological and pathological processes ranging from antigen presentation to T cell to neurodegenerative diseases. In several types of malignancies, a variety of EVs can be isolated from bodily fluids of cancer patients, and it has been reported that the number of circulating EVs seems to be higher than in healthy subjects. This increase correlates with poor prognosis. Data obtained from different groups clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 98 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…Exosomes are being increasingly examined as delivery vehicles for small molecule drugs, and large biological medications and in some disease situations. Exosomes have advantages of stability, bio‐compatibility, low immunogenicity and the ability to be externally loaded with a cargo . Exosomes have acceptable stability for storage and shipping, which are basic features required for drug delivery vehicles, and represent a cell‐free and manageable system.…”
Section: Use Of Micrornas and Exosomes For Treatment Of Hpv‐positive mentioning
confidence: 99%
See 3 more Smart Citations
“…Exosomes are being increasingly examined as delivery vehicles for small molecule drugs, and large biological medications and in some disease situations. Exosomes have advantages of stability, bio‐compatibility, low immunogenicity and the ability to be externally loaded with a cargo . Exosomes have acceptable stability for storage and shipping, which are basic features required for drug delivery vehicles, and represent a cell‐free and manageable system.…”
Section: Use Of Micrornas and Exosomes For Treatment Of Hpv‐positive mentioning
confidence: 99%
“…Exosomes have acceptable stability for storage and shipping, which are basic features required for drug delivery vehicles, and represent a cell‐free and manageable system. Recently, researchers have explored exosomes for the delivery of small interfering RNAs, miRNAs, short hairpin RNAs and anti‐inflammatory or anticancer drugs such as curcumin, paclitaxel or doxorubicin . Studies in a mouse model showed that exosomes with HPV‐specific activity could be helpful in CC immunotherapy (Figure ) .…”
Section: Use Of Micrornas and Exosomes For Treatment Of Hpv‐positive mentioning
confidence: 99%
See 2 more Smart Citations
“…(6) EVs typically range from 30nm to 2,000 nm in diameter (7) and can be broadly classified into exosomes, microvesicles and apoptotic bodies, according to their biogenesis. (7,8) While microvesicles and apoptotic bodies arise through direct blebbing off the membrane of a normal or apoptotic cell, respectively, exosomes are generated through the endolysosomal pathway. (7) Existing research recognises that an increased abundance of exosomes in cancer patients' blood (9,10) may play a role in the so-called cancer "field effect," in which cancer cells induce malignant changes in the surrounding healthy cells.…”
Section: Introductionmentioning
confidence: 99%